Dynamic / Thermochemical Method: A Novel Approach in The Synthesis of B4C Powder - Boussebha, Hamza; Bakan, Sinan; Kurt, Ali Osman (Elsevier, 2021)
The synthesis of high quality B4C powders with high purity, uniaxial shape and homogeneous size distribution, has been hard to obtain. Current production methods take place at temperatures above 1800 C, yielding high free carbon and large particle size. In this study, using a novel and patented approach, a reaction temperature of 1500 C for 1 h was sufficient to synthesize fine B4C powders from boron oxide (B2O3) and carbon black (C). This technique is based on the dynamic/thermochemical method (DTM), in which B2O3 and C powders are granulated before being charged into an atmosphere-controlled rotary type furnace. The granulation process and parameters of raw materials were the key to obtain high purity B4C powders, with equiaxed-grains and homogenous distribution with an average size of 10 μm.
Keywords: Boron Carbide; Thermochemical Method; Carbothermal Reduction; Advanced Ceramics